Math connects : Grade 1 - McGraw-Hill ,Glencoe (Columbus, OH Macmillan/McGraw-Hill, 2009)
With the Math Connects Kindergarten program, students learn math as they see that It's All Connected! They'll solve real-world problems such as creatures under the sea; emperors of the ice; and Read more...
Keywords: Mathematics -- Study and teaching (Primary) Mathematics -- Study and teaching (Elementary)